Aquaretics Use in Acute Decompensated Heart Failure (ADHF) Patients: A Literature Review - Norman Sukmadi; Kevin Surya; Arif Sejati (Acta Medica Indonesiana)
This is a literature review of the use of aquaretic in patients with acute decompensated heart failure (ADHF), including the physiologic function of vasopressin and its mechanism of action in heart failure patients, and aquaretic drugs with their respective risks and benefits. Vasopressin is one of several hormones that can cause hyponatremia and worsen congestion in ADHF patients. Aquaretics are a class of drugs that have an antagonistic effect on vasopressin receptors, especially V2R. Aquaretics use in ADHF patients can provide relief for congestive symptoms with no serious adverse effects. In-depth additional understanding regarding aquaretics may be useful for clinical judgments in treating ADHF patients.